Quantitative Analysis of Leverage Ratio on Earning-Per-Share of Property and Real Estate Sectors in Indonesia - Gaffar, Samsu; Uleng Akal, Andi Tenri (Manunggal Halim Jaya, 2021)
Objectiveness of our study is expected to provide the several contributions: (1) Theoretical benefits, the results of this study are expected to contribute to the development of economics, especially financial science, as material for developing insight into financial performance through operating leverage and financial leverage on earnings per share (EPS). This research was conducted on the Indonesia Stock Exchange (IDX). The research time taken in carrying out and completing this activity is scheduled for 3 (three) months, from July to September 2020. The population in this study is the property and real estate sector companies listed on the Indonesia Stock Exchange (IDX) from 2017-2019, totaling 62 companies. The method of determining the sample in this study used purposive sampling. The result of this study showed operating leverage has a positive and significant effect on earnings per share, financial leverage has no effect and is not significant on EPS, operating leverage and financial leverage simultaneously have a positive and significant effect on earnings per share. Based on the results of our demonstration of the analysis and discussion, several suggestions are put forward e.g., before investing in any company, an investor needs to pay attention to the level of earnings per share.